Azithromycin for uncomplicated severe acute malnutrition: study protocol for a pilot randomized controlled trial - Kieran S. O’Brien; Ali Sié; Clarisse Dah; Millogo Ourohire; Ahmed M. Arzika; Valentin Boudo; Elodie Lebas; William W. Godwin; Benjamin F. Arnold; Catherine E. Oldenburg (Pilot and Feasibility Studies, 2021)
Abstract Background Given the high risk of infectious mortality among children with severe acute malnutrition (SAM), the World Health Organization recommends routine administration of a broad-spectrum antibiotic like amoxicillin as part of the management of uncomplicated SAM. However, evidence for the efficacy of amoxicillin to improve nutritional recovery or reduce mortality has been mixed. With a long half-life and evidence of efficacy to reduce mortality in high-risk populations, azithromycin is a potential alternative to amoxicillin in the management of SAM. In this pilot study, we aim to compare the efficacy of azithromycin to amoxicillin to improve nutritional outcomes in children with uncomplicated SAM. Methods This pilot randomized controlled trial will enroll 300 children with uncomplicated SAM from 6 Centre de Santé et de Promotion Sociale in the Boromo health district in Burkina Faso. Eligible children are randomized to receive a single directly observed dose of oral azithromycin or a 7-day course of oral amoxicillin in addition to the standard package of care for uncomplicated SAM. Enrolled children are followed weekly until nutritional recovery, and all children return for a final study visit at 8 weeks after enrollment. Anthropometric indicators, vital status, and clinical outcomes are monitored at each visit and compared by arm. Primary feasibility outcomes include enrollment potential, refusals, loss to follow-up, and completeness of data collection. The primary clinical outcome is weight gain (g/kg/day) over the 8-week study period. Discussion This pilot trial will establish the feasibility of conducting a full-scale randomized controlled trial to evaluate alternative antibiotics in this setting and provide preliminary evidence for the efficacy of azithromycin compared to amoxicillin to improve outcomes for children with SAM. Trial registration This trial was first registered on clinicaltrials.gov on 26 June 2018 ( NCT03568643 ).